Adverse COVID‐19 outcomes in immune deficiencies: Inequality exists between subclasses. Issue 1 (10th August 2021) - Karakoc Aydiner, Elif; Bilgic Eltan, Sevgi; Babayeva, Royale; Aydiner, Omer; Kepenekli, Eda; Kolukisa, Burcu; Sefer, Asena Pinar; Yalcin Gungoren, Ezgi; Karabiber, Esra; Yucel, Esra Ozek; Ozdemir, Oner; Kiykim, Ayca; et al.
Abstract: Background: Genetic deficiencies of immune system, referred to as inborn errors of immunity (IEI), serve as a valuable model to study human immune responses. In a multicenter prospective cohort, we evaluated the outcome of SARS‐CoV‐2 infection among IEI subjects and analyzed genetic and immune characteristics that determine adverse COVID‐19 outcomes. Methods: We studied 34 IEI patients (19M/15F, 12 [min: 0.6‐max: 43] years) from six centers. We diagnosed COVID‐19 infection by finding a positive SARS‐CoV‐2 PCR test ( n  = 25) and/or a lung tomography scoring (CORADS) ≥4 ( n  = 9). We recorded clinical and laboratory findings prospectively, fitted survival curves, and calculated fatality rates for the entire group and each IEI subclass. Results: Nineteen patients had combined immune deficiency (CID), six with predominantly antibody deficiency (PAD), six immune dysregulation (ID), two innate immune defects, and one in the autoinflammatory class. Overall, 23.5% of cases died, with disproportionate fatality rates among different IEI categories. PAD group had a relatively favorable outcome at any age, but CIDs and IDs were particularly vulnerable. At admission, presence of dyspnea was an independent risk for COVID‐related death (OR: 2.630, 95% CI; 1.198–5.776, p  < .001). Concerning predictive roles of laboratory markers at admission, deceased subjects compared to survived had significantly higher CRP, procalcitonin, Troponin‐T, ferritin, and total‐lung‐score ( p  = .020, p  = .003, p  = .014, p  = .013, p  = .020; respectively), and lower absolute lymphocyte count, albumin, and trough IgG ( p  = .012, p  = .022, p  = .011; respectively). Conclusion: Our data disclose a highly vulnerable IEI subgroup particularly disadvantaged for COVID‐19 despite their youth. Future studies should address this vulnerability and consider giving priority to these subjects in SARS‐Cov‐2 therapy trials. Abstract : 34 IEI patients aged between 0.6 and 43 years, eight patients (23.5%) succumbed to COVID‐19, indicating a highly vulnerable condition to COVID‐19. Laboratory markers associated with mortality included elevated acute phase reactants, ferritin, troponin T, TLS, and reduced ALC levels, albumin, and baseline IgG. Coughing, dyspnea, CORADS category 4–6, and negative SARS‐CoV‐2 PCR at admission were among the predictors of lethal outcome. Abbreviations: ALC, absolute lymphocye count; CID, combined immune deficiency; COVID‐19, coronavirus infectious disease 2019; CRP, C‐reactive protein; F, female; ICU, intensive care unit; ID, immune dysregulation; IEI, inbor errors of immunity; Ig, immunoglobulin; M, male; PAD, predominantly antibody deficiency; PcT, procalcitonin; RTE, recent thymic emigrants; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2; Unfav, unfavorable.